The Characteristics of Society in Indonesian Based on the Hofstede Cultural Dimensions: Measuring the Five Indonesian Island - Setyaningrum, Ratih; Wijaya, Andi Rahadiyan; Subagyo, Subagyo (Talenta Publisher, 2022)
There is culturally plural happens in nowadays life context in many ethnicities, in the same space. This cultural diversity leads to different communication and attitude in social society. Â The difference between the two cultures, the bigger between two cultures exist, the bigger challenge to adapt. Previous research stated that Indonesia is one Hofstede cultural group. But based on its location, Indonesia has various ethnic and historical sites. By seeing all of them, this paper has aimed to measure, to classify, and to do mapping on Indonesian cultural dimension characteristics. It has some of research steps by considering culture, management, and clustering of Indonesian cultural dimensions. The measurement using Hofstede was conducted to on 805 respondents, analyzed by using principal component analysis and been clustered by using principal component analysis and clustered using the agglomeration hierarchy clustering method. Respondents were coming from Indonesian native live in Sumatra, Java, Kalimantan, Sulawesi, Kupang and Ambon. The result showed that Indonesian culture could be categorized into 4 cluster groups; furthermore, it can be classified into 2 dimensions: intrinsic characteristics (1); environmental and future characteristics (2). The dimension of intrinsic characteristics consists of the power distance index (PDI), collectivism (COLL), and masculinity (MAS). Â Â At the same time, the dimension of environmental and future characteristics consists of uncertainty avoidance (UAI) and long-term orientation (LTO). The result of this study is a cultural mapping in Indonesian society that a potentially contribute to developing cultural pattern in smart cities.